School Refusal Behavior from The Perspective of The Early School Age Limits - Tihnike, Dona (PT Literasi Nusantara Publisher, 2023)
This study discusses the relationship between elementary school entry age and school refusal in children and adolescents. This study uses the literature review method with narrative analysis to deepen knowledge about school refusal. The conclusion that can be drawn from this study is that school refusal is not a mere diagnosis of anxiety disorder but needs to be mentioned because it often appears in association with other psychiatric diagnoses. School refusal is difficulty attending school, associated with emotional distress, especially anxiety and depression. It must be distinguished from other forms of school absences, such as truancy and disordered conduct, and the child not having associated antisocial behavior, such as lying, stealing, or vandalizing. Children who experience school refusal require personal assessment and treatment, and each child may have different causes that require further treatment. The most appropriate treatment is a treatment that suits the child's needs.